Synthesis Of Fatty Acid Methyl Esters (FAME) From Palm Oil Via Non-Catalytic Supercritical Fluid Reaction - Tan, Kok Tat (2011)
Palm oil is abundantly available in Malaysia and has been shown to be a promising feedstock in fatty acid methyl esters (FAME) or biodiesel production compared to other vegetable oils. In the present study, palm oil was utilized as the source of triglycerides in supercritical fluid reactions. The solvents that were investigated in this study were methanol, methyl acetate and dimethyl carbonate. An experimental system was successfully designed and fabricated for supercritical fluid (SCF) reaction. The non-catalytic SCF reactions were carried out with reaction temperature varying from 300°C to 400°C, molar ratio of solvent to oil from 10 to 50 mol/mol and reaction time of 5 to 60 minutes.